Regenerative medicine in dental and oral tissues: Dental pulp mesenchymal stem cell - Sudiono, Janti; Oka, Ciptadhi Tri; Djamil, Melanie S; Sandra, Ferry (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Background. Regenerative medicine is a new therapeutic modality using cell, stem cell and tissue engineering technologies. Purpose. To describe the regenerative capacity of dental pulp mesenchymal stem cell. Review. In dentistry, stem cell and tissue engineering technologies develop incredibly and attract great interest, due to the capacity to facilitate innovation in dental material and regeneration of dental and oral tissues. Mesenchymal stem cells derived from dental pulp, periodontal ligament and dental follicle, can be isolated, cultured and differentiated into various cells, so that can be useful for regeneration of dental, nerves, periodontal and bone tissues. Tissue engineering is a technology in reconstructive biology, which utilizes mechanical, cellular, or biological mediators to facilitate regeneration or reconstruction of a particular tissue. The multipotency, high proliferation rates and accessibility, make dental pulp as an attractive source of mesenchymal stem cells for tissue regeneration. Revitalized dental pulp and continued root development is the focus of regenerative endodontic while biological techniques that can restore lost alveolar bone, periodontal ligament, and root cementum is the focus of regenerative periodontic. Conclucion. Dentin-derived morphogens such as BMP are known to be involved in the regulation of odontogenesis. The multipotency and angiogenic capacity of DPSCs as the regenerative capacity of human dentin / pulp complex indicated that dental pulp may contain progenitors that are responsible for dentin repair. The human periodontal ligament is a viable alternative source for possible primitive precursors to be used in stem cell therapy.